2001
DOI: 10.1080/10668920150218461
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Recruitment Success for Two-Year College Students of Color

Abstract: The increasing proportion of students of color enrolled in secondary institutions makes the issue of their recruitment into postsecondary institutions an increasingly important concern in higher education. Data from a national survey of chief student affairs of cers (CSA Os) on recruitment barriers and strategies for students of color were merged with 1995 National Center for Education Statistics Integrated Postsecondary Education Data System Fall Enrollment Survey data. A regression analysis was conducted to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Land grant institutions are now experiencing the future predicted by NASULGC. According to U.S. Census Bureau data from 2000, approximately 30% of the U.S. population is a racial or ethnic minority group (Talbert & Edwin, 2007) and 28.7% of traditional college-aged students are African American or Hispanic (Opp, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Land grant institutions are now experiencing the future predicted by NASULGC. According to U.S. Census Bureau data from 2000, approximately 30% of the U.S. population is a racial or ethnic minority group (Talbert & Edwin, 2007) and 28.7% of traditional college-aged students are African American or Hispanic (Opp, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural education researchers have documented barriers to minority students entering the field; these barriers have been operationally defined within education research as attitudinal barriers and structural barriers (Opp, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Kirst (2001b) called for the extension of dual credit to a larger segment of the high school population to include underrepresented students and students other than the academic elite. Research has shown that dual credit programs can have a very positive effect on the postsecondary performance of underachievers, minority, and at-risk students (Opp, 2001;Brigham, 1989;Hugo, 2001;Lieberman, 1986;. Johnstone and Maloney (1998) found that increased access and successful student performance in dual credit courses positively influenced the transition between high school and postsecondary education and thereby the improving the overall productivity and efficiency of student learning.…”
Section: Research Problemmentioning
confidence: 99%
“…Opp (2001) investigated institutional characteristics that assisted in the recruitment of Black students to two-year colleges. The data were drawn from a national survey of chief student affairs officers on recruitment barriers and strategies for students of color.…”
Section: Ethnicity and Socio-economic Backgroundmentioning
confidence: 99%
See 1 more Smart Citation